Self-actualization and subjectivity in young women looking for a new job - N. A. Tsvetkova (Вестник университета)
The subject of the research is self-actualization and subjectivity in women looking for a new job, and the goal is to determine the features of these processes and their connection. The article uses the method of psychological testing, i.e. J.E. Aleshina’s adaptation of E. Shostrom’s SAT test, M.A. Shchukina’s LPSD test, etc. The sample included 74 women. The moderate general level of subjectivity with tendency to high on indicators of integrity and self-value has been stated. A direct close connection between self-actualization and subjectivity has been revealed. The data obtained is important for assessing the sociopsychological readiness of women to independently solve the employment problem. The research needs to be continued considering gender specifics. The results of the study are valuable for practical psychologists in terms of helping young women who find it difficult to realize their intentions to change their job due to problematic and disharmonious self-actualization as well as underdeveloped subjectivity.